2009
DOI: 10.3109/08923970902971101
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reaction between proteins ofLarrea divaricataCav. (jarilla) and proteins of Gram-negative bacteria

Abstract: Larrea divaricata is an abundant plant of northwest of Argentina used to treat different pathologies. We aimed to characterize the immunogenicity of proteins from a partially purified crude aqueous extract (JPCE) of jarilla. We evaluated the cross reaction between JPCE and whole cell-bacterial proteins (W-CBP) of Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris, and Klebsiella pneumoniae using a mouse anti-JPCE serum. Protein profiles of JPCE and W-CBP were analyzed. For JPCE, 18 bands were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that proteins from the crude aqueous extract of L. divaricata administered with adjuvants to mice can induce a good specific immune response, showing crossreaction with proteins of different Gram-negative bacteria such as Escherichia coli, Proteus vulgaris, Klebsiella pneumoniae and Pseudomonas aeruginosa. In this sense, the IgG and IgA antibodies elicited by immunization with L. divaricata proteins were able to opsonize these bacteria and favor phagocytosis (de Anaya et al, 2009;Sasso et al, 2012;Canale et al, 2018). The anti-L divaricata proteins antiserum can inhibit enzymatic activities of P. aeruginosa such as the hemolytic activity of soluble cell proteins, the protease activity and Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas / 754 extracellular proteins by 100%, 55%-70% and 44% and 95%, respectively (Sasso et al, 2012).…”
Section: Immunomodulatory Effects: Pro-and Antiinflammatory Effectsmentioning
confidence: 99%
“…It has been demonstrated that proteins from the crude aqueous extract of L. divaricata administered with adjuvants to mice can induce a good specific immune response, showing crossreaction with proteins of different Gram-negative bacteria such as Escherichia coli, Proteus vulgaris, Klebsiella pneumoniae and Pseudomonas aeruginosa. In this sense, the IgG and IgA antibodies elicited by immunization with L. divaricata proteins were able to opsonize these bacteria and favor phagocytosis (de Anaya et al, 2009;Sasso et al, 2012;Canale et al, 2018). The anti-L divaricata proteins antiserum can inhibit enzymatic activities of P. aeruginosa such as the hemolytic activity of soluble cell proteins, the protease activity and Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas / 754 extracellular proteins by 100%, 55%-70% and 44% and 95%, respectively (Sasso et al, 2012).…”
Section: Immunomodulatory Effects: Pro-and Antiinflammatory Effectsmentioning
confidence: 99%
“…Experimental studies with L. divaricata extracts have demonstrated fungotoxic and antimicrobial activity, (2)(3)(4) antitumoral effects, (5)(6)(7) immunostimulatory effects (8,9) and cross-reaction with proteins of Gramnegative bacteria. (10) Pseudomonas aeruginosa is a Gram-negative bacterium considered as an opportunistic pathogen which can cause severe and lethal infections in vulnerable hosts due to its ability to secrete many extracellular factors that are associated with the virulence. (11) It is a major health problem in hospitals, especially with immunocompromised patients (i.e.…”
Section: Introductionmentioning
confidence: 99%